2010
DOI: 10.1039/b919298k
|View full text |Cite
|
Sign up to set email alerts
|

Direct template-free electrochemical growth of hexagonal CuSn tubes from an ionic liquid

Abstract: Free standing hexagonal hollow copper-tin tube arrays are formed by direct cathodic electrolysis in the 1-ethyl-3-methylimidazolium dicyanamide ionic liquid containing Cu(I) and Sn(II) without using a template at 313 K.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(15 citation statements)
references
References 27 publications
1
14
0
Order By: Relevance
“…Figure 3 shows the SEM images of the deposits obtained on a GC substrate by potentiostatic cathodic reduction at ¹2.0 V. Tubular deposits with the inner diameter of 1-1.5 µm were obtained in addition to granular deposits. The deposits with a hexagonal tube shape were obtained in the electrodeposition of not only Sn 7 but also Cu-Sn 12 and Cu-Zn 13 alloys in ionic liquids. Hsieh et al described generation of such pyramidal tubular deposit was due to preferential growth of periphery parts due to the overpotential gradient between the central and periphery parts of nuclei.…”
Section: Resultsmentioning
confidence: 99%
“…Figure 3 shows the SEM images of the deposits obtained on a GC substrate by potentiostatic cathodic reduction at ¹2.0 V. Tubular deposits with the inner diameter of 1-1.5 µm were obtained in addition to granular deposits. The deposits with a hexagonal tube shape were obtained in the electrodeposition of not only Sn 7 but also Cu-Sn 12 and Cu-Zn 13 alloys in ionic liquids. Hsieh et al described generation of such pyramidal tubular deposit was due to preferential growth of periphery parts due to the overpotential gradient between the central and periphery parts of nuclei.…”
Section: Resultsmentioning
confidence: 99%
“…The different sizes of the prisms may result from the initial nucleation time which is related to the concentration of Cu(I) and Sn(II). Higher concentration results from nucleation more easily produced and earlier nucleation formed larger prisms because there is a longer time period for the prism to grow [10].…”
Section: Methodsmentioning
confidence: 99%
“…As known to all, electrodeposition is widely used by industrial production and lab experiments due to its simple process, easy operation, uniform sedimentation, and so on. Furthermore, ionic liquids usually have a wide electrochemical window and show ideal electrolytes for electrodeposition application; it can especially obtain different microstructural platings in ILs [10,11]. Sun et al have reported a method that allowed electrochemical growth of metal alloys from ILs, obtaining a nanotube alloy [11] and a nanowire alloy [12].…”
Section: Introductionmentioning
confidence: 99%
“…By adjusting deposition potential and solution composition, PdCu, PdSn and PdNi alloys with good electrocatalytic capability were prepared. In an interesting report by Sun and coworkers, free‐standing single crystalline hexagonal Cu 10 Sn 3 hollow tubes were obtained by direct cathodic deposition in [Emim]DCA containing 0.1 m Cu I and 0.05 m Sn II at a low current density of −0.4 mA cm −2 . In a further work, hierarchical single‐crystalline Cu 3 Sn nanobrushes were obtained as the Cu I /Sn II concentration ratio was changed to 1:2.…”
Section: Direct Electrodeposition From Ilsmentioning
confidence: 99%